Energy storage property of (Pb0.97La0.02)(Zr0.5Sn0.4Ti0.1)O3-(Na0.5Bi0.5)0.94Ba0.06TiO3 ceramics: Effects of antiferroelectric-relaxor transition and improved breakdown strength. Issue 8 (July 2020) - Li, Ling; Wang, Rui-Xue; Gu, Zheng-Bin; Lu, Ming-Hui; Zhu, Mingwei; Zhang, Shan-Tao
Abstract: (1- x )(Pb0.97 La0.02 )(Zr0.5 Sn0.4 Ti0.1 )O3 - x (Na0.5 Bi0.5 )0.94 Ba0.06 TiO3 ( x = 0 ∼ 0.4) ceramics have been prepared and investigated. The ceramics consist of perovskite solid solution matrix and precipitated, isolated SnO2 particle, resulting in 0–3 type composite structure. With increasing x value, the room temperature crystal structure of perovskite solid solution transforms from tetragonal to pseudocubic, therefore, the electrical property evaluates form robust antiferroelectric at x = 0, metastable antiferroelectric at x = 0.1, and then relaxor ferroelectric at x > 0.1. Moreover, the breakdown strength is enhanced due to the composite structure and reaches maximum value of 190 kV/cm at x = 0.2. Both the phase transition and enhanced breakdown strength are helpful to improve energy storage property, the x = 0.2 ceramic shows largest recoverable energy density wrec of 1.84 J/cm 3, discharge efficiency η of 86.6 %. Especially, both wrec and η illustrates significantly improved thermal stability within 25−125 °C.